Elementary School Teachers Received Training on Using Google Forms for Assessing Students' Learning During the Covid-19 Pandemic - Afib Rulyansah; Rachma Rizqina Mardhotillah; Rizqi Putri Nourma Budiarti; Jauharotur Rihlah; Surnia Maulidah Azzahra (Utan Kayu Publishing, 2023)
As a result of the spread of the COVID-19 virus, traditional classroom instruction has had to be replaced by online, asynchronous distance learning. The evaluation of students' progress is one area that has room for improvement. Teachers can use a wide variety of programs to administer online learning evaluations. The Google form is frequently utilized as an online evaluation tool. There have been many successful online assessments conducted using Google Forms, including blind evaluation exercises, assessments of lecturer effectiveness, and assessments of alternative pedagogical approaches. Training is conducted via the online meeting tool Zoom, and participants are given assignments to complete as part of the process. Elementary school educators are the target audience for this workshop. There were 10 educators from SDN Tegalrejo in the Dringu District of the Probolinggo Regency who participated in this training. There are three phases to this training: pre-training, training, and post-training evaluation and adjustment. The training's outcomes, beginning with the identity page and continuing through question entry, answer key entry, and scoring, are generally consistent with the training's tutorials. The majority of those polled (95%) found the training to be beneficial. The majority of respondents agreed or strongly agreed that the training provided was beneficial and appropriate for their needs during their time spent learning online.